Economic expertise of investment project "HOUSEHOLD HOUSE" - Izmaylovа K. (Ways to Improve Construction Efficiency, 2019)
Мethods and Are an example of economic investment expertise in the construction and operation of "Apartment dwelling house" during the first 17 years. Use classic methods and indicators for assessing the effectiveness of investment jekonoicheskoj, namely: the payback period, the average rate of return, net present value, internal rate of return.